Carcass and meat quality of young Angus steers with different growth potential finished exclusively grass-fed or corn supplemented - Santin I.A.* (2021)
© 2021, The Author(s), under exclusive licence to Springer Nature B.V.Beef cattle production has a large variety of systems with different performance and technology levels. This study compared young Angus steers carcass and meat quality traits of high growth potential early-finished animals fed exclusively on pasture with low growth potential late-finished animals. Besides the grazed forage, the low growth potential group received corn grain at 0.8% of their body weight right after the slaughtering of the first group. Following weaning, the 20 steers grazed pastures composed of oat, ryegrass, and clovers. At winter’s onset, animals were moved to native pastures improved with fescue and clovers. The supplemented period of late steers began when the first group of ten early-finished animals reached the requirements for slaughter. Supplementation ended when the animals got the slaughter requirements. The high growth potential steers showed a ribeye area (P < 0.0001) and a Longissimus muscle width highly significantly (P < 0.0001) superior to the low growth group. However, corn-supplemented animals showed better dressing percentage (P < 0.0001), subcutaneous fat thickness (P < 0.0001), marbling (P < 0.0001), and muscle (P = 0.0033) scores, but lower shear force (P = 0.0001). The finishing system did impact fat lightness (L*; P = 0.0234) at the slaughter time. Grass-fed animals showed higher red-green color parameter (a*) values than corn supplemented on fat at 24 h (P = 0.0439) but lower hue angle (P = 0.0418). The consumer panel showed better results for tenderness and general acceptability for supplemented animals beef compared to grass-fed. The supplementation resulted in a higher carcass standardization. It also provided higher PUFA: MUFA and n-6: n-3 ratios, and a higher amount of n-3. Supplemental corn grain did not have adverse effects upon the beneficial effects to human health of the grass-fed beef.